IMPLEMENTASI TEORI BELAJAR SOSIAL: STUDI KASUS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DALAM KAITAN PENINGKATAN HASIL BELAJAR KOGNITIF KELAS III SD NEGERI 015 MUARA KOMAN - Megawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of the cooperative learning model with a social theory approach in the Pancasila Education subject in Grade III at SD Negeri 015 Muara Koman still faces challenges. Therefore, the purpose of this study is to determine the cognitive learning outcomes in the Pancasila Education subject for Grade III at SD Negeri 015 Muara Koman. The research method used is qualitative research with respondents including teachers, students, and the principal. The selection of respondents was done through purposive sampling based on the research objectives. Snowball sampling was applied through the involvement of participants in accordance with the respondents.The research procedure began with the researcher preparing instruments and learning tools differentiated by the humanistic learning theory approach. The research was conducted through interviews and observation techniques. Data analysis was carried out through interim conclusions and final conclusions drawn during the interview process.The research findings show that the teacher respondent had prepared, implemented, and evaluated the implementation of cooperative learning based on a social approach in Grade III at SDN 015 Muara Koman. The student respondents had prepared, participated in, and achieved cognitive learning outcomes. The principal respondent had facilitated the preparation, implementation, and evaluation of the cooperative learning implementation using the social approach, resulting in improved cognitive learning outcomes among the students